Quality of basic emergency obstetric and newborn care services from patients’ perspective in selected public health centers in Addis Ababa, Ethiopia 2022: A cross-sectional study - Willi Bahre; Achamyelesh Tadele; Finot Debebe (PLoS ONE, 2025)
Background The majority of maternal and neonatal deaths occur within the first 24 hours of birth. To minimize maternal as well as neonatal morbidity and mortality, it is important to supply quality Basic Emergency Obstetric and Newborn Care. Basic emergency obstetric and newborn care services prevent immediate obstetric problems. There have been studies in Ethiopia that have looked at the availability of EmONC services. However, from the clients’ perspective and experience, there is insufficient knowledge of quality BEmONC services. Objective To assess the quality of basic emergency obstetric and newborn care (BEmONC) services and associated factors from the perspective of mothers in selected public health centers in Addis Ababa, Ethiopia, 2022. Methods A facility-based cross-sectional study was used among mothers receiving at least one of the signal functions of BEmONC services. A total of 377 mothers were enrolled. Eleven public health centers, one from each of the 11 sub-cities, were selected by simple random sampling. Respondents were chosen by a systematic random sampling method. A structured questionnaire from Open Data Kit version 2022.1.2 was used. Finally, it was exported to SPSS version 26 for analysis. Bivariate analysis at a P-value of 0.25 and multivariable analysis at a P-value of 0.05 were applied. Results The overall quality of BEmONC services from the mothers’ perspective was 56.9%. Mothers who paid for services had lower odds of rating the quality as good compared to those who received services for free (AOR =  0.564; 95% CI: 0.327–0.971). Additionally, mothers aged 20 to 24 years had a lower likelihood of viewing the quality as good compared to those older than 35 years (AOR =  0.362; 95% CI: 0.157–0.837). However, mothers who were accompanied by relatives had significantly higher odds of rating the quality as good than those who were alone (AOR =  18.557; 95% CI: 3.844–89.588). Regarding monthly income, respondents with an average monthly income of less than 1,500 ETB had higher odds of rating the quality as good compared to those earning more than 6,000 ETB (AOR =  2.429; 95% CI: 1.026–5.753). Conclusion and recommendation The total quality of BEmONC services from the perspective of mothers was suboptimal. It was predicted by age, monthly income, presence of a companion, and payment. This study strongly recommends that more should be done to ensure that the services given are more client-centered.